2018
DOI: 10.1111/1759-7714.12913
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors and outcome of surgically treated patients with brain metastases of non‐small cell lung cancer

Abstract: BackgroundBrain metastases (BM) are a common consequence of lung cancer and surgery is effective; however, the factors affecting survival after surgery are unclear. The aim of this study was to identify the outcomes and prognoses of post‐metastasectomy patients with BM from non‐small cell lung cancer (NSCLC) at a single institution over a 15‐year period.MethodsNSCLC patients who had undergone BM surgery were retrospectively identified. Survival was analyzed using the Kaplan–Meier curve, and univariate and mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Our results demonstrate a significant, independent association between KPS score and LOS, discharge disposition, and hospital charges. While research has shown KPS to be strongly associated with overall and progress-free survival among metastatic brain tumor patients, there has been limited research into how well KPS can prognosticate high-value care outcomes [ 28 , 29 ]. To our knowledge, the present study is the first to utilize KPS to predict individualized risk of high-value care outcomes specifically among patients undergoing surgical treatment of metastatic brain tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Our results demonstrate a significant, independent association between KPS score and LOS, discharge disposition, and hospital charges. While research has shown KPS to be strongly associated with overall and progress-free survival among metastatic brain tumor patients, there has been limited research into how well KPS can prognosticate high-value care outcomes [ 28 , 29 ]. To our knowledge, the present study is the first to utilize KPS to predict individualized risk of high-value care outcomes specifically among patients undergoing surgical treatment of metastatic brain tumors.…”
Section: Discussionmentioning
confidence: 99%
“…The KPS assesses patients' functional status. A KPS of more than 80 indicates that patients can take care of themselves (She et al 2019). When patients' KPS is below 70, ICIs should be used with caution (Thompson et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The initial onset of brain metastases is generally considered an unfavorable prognostic factor that increases the risk of death [35]. In a recent study, Korpanty et al [1] found no significant survival difference in patients with and those without brain metastases at diagnosis.…”
Section: Discussionmentioning
confidence: 99%